A fundamental misunderstanding of risk: The bias associated with the annualized calculation of standard deviation - Matthew W. Burkett; William T. Scherer (Cogent Economics & Finance, 2020)
Quantifiable, measurable risk is of critical importance when making data-driven decisions in finance and investment management, but what if the generally accepted practice of the investment industry for calculating risk possessed incorrect mathematical assumptions and embedded biases? This piece revisits the discussion surrounding the methodology used to calculate annualized standard deviation statistics commonly used when reporting the performance of investment products. It goes on to present a new example illustrating the bias when applied to an efficient frontier.
Keywords: 330; bias; efficient frontier; investment performance; Risk; standard deviation; volatility